Frequency of In-Hospital Mortality in Patients with Upper Gastrointestinal Bleeding (UGIB) Due to Liver Cirrhosis - Dilber, Mehwish; Sahito, Abdul Aziz; Memon, Waseem Raja; Phul, Zafar Ullah; Zarrar, Muhammad; Khokhar, Riaz Hussain (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Upper Gastrointestinal haemorrhage is a common medical emergency, and a fatality in liver cirrhosis patients The most common complication of portal hypertension in liver cirrhosis patients is esophageal variceal bleeding. This clinical survey was conducted to determine the mortality rate of cirrhotic patients with UGI bleeding in-hospital. In addition to those clinical presentations of patients, pre- and post-endoscopic findings, re-bleeding, and other outcomes were also studied during hospitalization.Methods: This cross-sectional study employed a non-probability consecutive sampling technique to collect data over six months. A total of 202 patients were included in the sample, with a 95% confidence level and a 5% margin of error.   Data were collected from participants meeting through clinical examination, endoscopy, and laboratory tests. Samples were analyzed for relevant parameters such as hemoglobin levels and bleeding source. All data was documented into pre-designed proformas, then the collected data was used to analyze it using SPSS Statistics 30.0.0.Results: The main cause of UGIB in cirrhotic patients was rupture of esophageal and gastric varices. However, 70% of bleeding in the variceal bleeding group was due to esophageal, and 9.5% was dedicated to gastric varices. Whereas the UGI bleeding from non-variceal patients was due to peptic ulcer it was around 20.5% of total UGIB cirrhotic patients.Conclusion: The findings revealed that variceal bleeders have a significant chance of rebleeding, and those patients have higher mortality chances than non-variceal bleeders. The proper clinical presentation of patients, their treatment, and management, including endoscopy and its outcomes, are critical to formulating the important guidelines for liver cirrhosis and UGI haemorrhage patients.